1989
DOI: 10.1080/07924259.1989.9672067
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of last reproduction steps in tsetse flies (Glossina:Diptera)

Abstract: and 2Newoendocrinologie des Znsectes, CNRS UA 669, Universitt! P. and M. Curie, 12, rue Cuvier, 75252 Paris Ckdex 05, FranceThe regulation of ovulation and parturition, in the viviparous tsetse flies, constitutes a very pncisely adjusted mechanism. Indeed the process of vitekgenesis takes places, in one oocyte only, during the incubation period when the larva is nourished in utero on milk produced by the mother. Neuropeptides, biogenic amines, neurotransmitters as well as ecdysone, and 20-hydroxyecdysone and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…A complementary screening of several organs of the genital tract was performed using a bioassay based on the recording of the contractile activity of the distal oviduct described by Henry et al, (1997). These investigations revealed a myotropic activity in the ovary extract similar to what has been observed for insects, for example tsetse flies (Grillot and Raabe, 1989). Previously, Henry and BoucaudCamou (1993) had shown that the ovary was involved in the control of egg capsule edification.…”
Section: Introductionmentioning
confidence: 91%
“…A complementary screening of several organs of the genital tract was performed using a bioassay based on the recording of the contractile activity of the distal oviduct described by Henry et al, (1997). These investigations revealed a myotropic activity in the ovary extract similar to what has been observed for insects, for example tsetse flies (Grillot and Raabe, 1989). Previously, Henry and BoucaudCamou (1993) had shown that the ovary was involved in the control of egg capsule edification.…”
Section: Introductionmentioning
confidence: 91%